2018
DOI: 10.1038/s41467-018-04529-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier opening in Alzheimer’s disease using MR-guided focused ultrasound

Abstract: Magnetic resonance-guided focused ultrasound in combination with intravenously injected microbubbles has been shown to transiently open the blood–brain barrier, and reduce beta-amyloid and tau pathology in animal models of Alzheimer’s disease. Here, we used focused ultrasound to open the blood–brain barrier in five patients with early to moderate Alzheimer’s disease in a phase I safety trial. In all patients, the blood–brain barrier within the target volume was safely, reversibly, and repeatedly opened. Openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
576
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 696 publications
(630 citation statements)
references
References 38 publications
13
576
1
1
Order By: Relevance
“…Follow up studies might also control for blood brain barrier opening, [23] although our energy levels render it unlikely, that this occurred in our subjects. The simulations, laboratory, and in vivo animal measurements also indicate broad safety margins according to the current state of acquired data.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Follow up studies might also control for blood brain barrier opening, [23] although our energy levels render it unlikely, that this occurred in our subjects. The simulations, laboratory, and in vivo animal measurements also indicate broad safety margins according to the current state of acquired data.…”
Section: Resultsmentioning
confidence: 95%
“…The application of ultrasound for brain therapy has become a hot topic as it bears the potential for providing a new class of semi-invasive (ablation [20][21][22] or blood brain barrier opening [23] ), or noninvasive (brain stimulation) brain therapies. However, Adv.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of PRGFRaÀinduced BBB disruption is not understood, but intriguingly, the expression of Pdgfra is largely restricted to perivascular fibroblasts among the different cell types of the NVU [17]. An alternative approach is based on focused ultrasound, which may transiently open BBB to release toxic Ab from AD patients [177]. As discussed above, pericytes are important for the constriction of capillaries and reduced CBF observed in the post-stroke situation [39,40].…”
Section: Toward Therapy Developmentmentioning
confidence: 99%
“…For clinical imaging using DEFINITY as a contrast agent, 20 μL/kg is the maximal dose recommended by the manufacturer [40], which has been shown to successfully increase BBB permeability following FUS in rodents [39, 41]. The first clinical trial in AD patients used DEFINITY at a dose of 4 μL/kg for FUS-mediated BBB opening in humans [16]. Using a clinical imaging dose of DEFINITY microbubbles for FUS-mediated BBB permeability, McMahon et al reported no acute inflammatory response, hemorrhage, or edema following treatment.…”
Section: Notesmentioning
confidence: 99%
“…1). Focused ultrasound, combined with microbubbles and guided by magnetic resonance imaging (MRI), has been applied to open the BBB in a safe, noninvasive, and reversible manner in targeted areas ofbrain in animal models [15] and, most recently, in AD patients [16]. MRI-guided FUS (MRIgFUS)-mediated delivery of rAAVs to targeted areas of the brain and spinal cord can be achieved with systemic doses which are up to 100 times lower than those conventionally used with rAAVs capable of crossing the BBB [11, 15, 1720].…”
Section: Introductionmentioning
confidence: 99%